The Influence of Government Regulations on Auditing Practices: A Qualitative Research - Santoso, Ferdi; Wijaya, Anggi; Pramudita, Cindy; Permata, Dita; Suryani, Eka (Manunggal Halim Jaya, 2021)
This qualitative research investigates the influence of government regulations on auditing practices, aiming to provide insights into how regulatory frameworks shape audit methodologies and impact audit quality. The study employs semi-structured interviews, document analysis, and participant observation to gather data from key stakeholders in the auditing profession. Thematic analysis is used to analyze the qualitative data, revealing the complex interplay between regulatory compliance, audit methodologies, and audit quality. The findings indicate that auditors adapt their procedures and practices to meet regulatory requirements while maintaining audit efficiency and effectiveness. Regulatory compliance serves as a cornerstone of audit practice, influencing the allocation of resources and the adoption of risk-based audit methodologies. Moreover, the study explores the impact of regulatory reforms, such as the Sarbanes-Oxley Act of 2002, on audit quality and financial reporting integrity. While some participants perceive regulatory reforms positively, others express concerns about the regulatory burden and unintended consequences of compliance. Document analysis further underscores the mixed perceptions surrounding the effectiveness of regulatory oversight mechanisms in deterring audit failures and enhancing auditor accountability. Overall, the study contributes to a deeper understanding of the intricate relationship between government regulations and auditing practices, with implications for policymakers, regulators, audit practitioners, and other stakeholders striving to enhance the effectiveness of regulatory regimes and promote transparency and integrity in financial reporting.